Survival of Escherichia coli in common garden mulches spiked with synthetic greywater. (2nd April 2017) - Boyte, S.; Quaife, S.; Horswell, J.; Siggins, A.
Abstract : Abstract: Reuse of domestic wastewater is increasingly practiced as a means to address global demands on fresh water. Greywater is primarily reused via subsurface irrigation of gardens, where the soil environment is seen to be an integral part of the treatment process. The fate of biological contaminants (i.e. pathogens) in the soil is reasonably well understood, but their persistence and survival in soil cover layers is largely unexplored. This study investigated the ability of Escherichia coli to survive in common soil cover layers. Three garden mulches were investigated: pea straw mulch, a bark‐based mulch and a coconut husk mulch. Each mulch was treated with an E. coli solution, a synthetic greywater with E. coli, or a freshwater control. Escherichia coli was applied at 1 × 10 4  most probable number (MPN) per g dry weight mulch. Subsamples were temporally analysed for E. coli . The bark and coconut husk mulches showed a steady decline in E. coli numbers, while E. coli increased in the pea straw mulch for the duration of the 50 days experiment, peaking at 1·8 × 10 8  MPN per g dry weight mulch. This study highlighted the importance of selection of a suitable material for covering areas that are subsurface irrigated with greywater. Significance and Impact of the Study: Potential for microbial contamination is one of the limiting factors for domestic greywater reuse. Although subsurface irrigation is considered to be one of the lowest risk applications, there is still a possibility of microbes reaching the soil surface if the environmental conditions are not favourable or if soil movement inadvertently exposes the irrigation line. In these circumstances, the soil cover layer may be contaminated by greywater microbes. This study assesses the survival rates of the pathogen indicator organism Escherichia coli in three soil cover materials commonly used worldwide and makes clear recommendations to facilitate the safe reuse of domestic greywater. Abstract : Significance and Impact of the Study: Potential for microbial contamination is one of the limiting factors for domestic greywater reuse. Although subsurface irrigation is considered to be one of the lowest risk applications, there is still a possibility of microbes reaching the soil surface if the environmental conditions are not favourable or if soil movement inadvertently exposes the irrigation line. In these circumstances, the soil cover layer may be contaminated by greywater microbes. This study assesses the survival rates of the pathogen indicator organism Escherichia coli in three soil cover materials commonly used worldwide and makes clear recommendations to facilitate the safe reuse of domestic greywater.